Exploiting Language Variation to Better Understand the Cognitive Consequences of Bilingualism - Takahesu Tabori, Andrea A.; Mech, Emily N.; Atagi, Natsuki (Frontiers in Psychology, 2018)
Within the past decade, there has been an explosion of research investigating the cognitive consequences of bilingualism. However, a controversy has arisen specifically involving research claiming a “bilingual advantage” in executive function. In this brief review, we re-examine the nature of the “bilingual advantage” and suggest three themes for future research. First, there must be a theoretical account of how specific variation in language experience impacts aspects of executive function and domain general cognition. Second, efforts towards adequately characterizing the participants tested will be critical to interpreting results. Finally, designing studies that employ converging analytical approaches and sensitive methodologies will be important to advance our knowledge of the dynamics between bilingual language experience and cognition.